2012
DOI: 10.1103/physrevlett.108.077207
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nonuniformity and Thermal Hysteresis of Magnetism in a Manganite Thin Film

Abstract: We measured the chemical and magnetic depth profiles of a single crystalline (La(1-x)Pr(x))(1-y)Ca(y)MnO(3-δ) (x=0.52±0.05, y=0.23±0.04, δ=0.14±0.10) film grown on a NdGaO(3) substrate using x-ray reflectometry, electron microscopy, electron energy-loss spectroscopy, and polarized neutron reflectometry. Our data indicate that the film exhibits coexistence of different magnetic phases as a function of depth. The magnetic depth profile is correlated with a variation of chemical composition with depth. The therma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 32 publications
(24 reference statements)
9
45
0
Order By: Relevance
“…The lattice mismatch strains at room temperature in the two in-plane directions are δ 110 = 0.49% and δ 001 = 0.26% [17]. The epitaxial growth and composition of our thin films have been confirmed earlier using x-ray reflectivity, neutron reflectivity, and electron energy loss spectroscopy [11,21]. We emphasize that these properties of the as-grown film minimize the possibility of extrinsic effects due to inhomogeneous strain and chemical inhomogeneities and we found that these qualities of our thin films are essential for the observation of anisotropic electric field effects.…”
supporting
confidence: 76%
“…The lattice mismatch strains at room temperature in the two in-plane directions are δ 110 = 0.49% and δ 001 = 0.26% [17]. The epitaxial growth and composition of our thin films have been confirmed earlier using x-ray reflectivity, neutron reflectivity, and electron energy loss spectroscopy [11,21]. We emphasize that these properties of the as-grown film minimize the possibility of extrinsic effects due to inhomogeneous strain and chemical inhomogeneities and we found that these qualities of our thin films are essential for the observation of anisotropic electric field effects.…”
supporting
confidence: 76%
“…Elucidating the competition between the energetically degenerate phases is crucial to harnessing macroscopic properties such as CMR and metal-insulator transition in such complex materials. Although manganites have been intensively studied for several decades, new insights continue to emerge on the characteristics and the dynamic evolution of magnetic domains [21][22][23], shedding light on the complex behaviors of competing phases in strongly correlated electron systems.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the symmetry breaking thereby takes place. The hysteresis, a nonequilibrium phenomenon obtained typically as the temperature of the system is varied, is one of the most interesting topics that have been studied in various fields such as the molecular switching using the spin crossover [121,122,123], the temperature driven metal-insulator transition in the solid-state devices [124,125] and the antifreeze proteins in the bionic systems [126,127]. The phenomenon of thermal hysteresis was also reported in the mean-field model [128], for which the closed hysteresis loop area (A) scales with the change rate of temperature R T as,…”
Section: Critical Slowing Downmentioning
confidence: 99%